Deep Refrains : Music, Philosophy, and the Ineffable - Gallope, Michael (University of Chicago Press, 2017)
We often say that music is ineffable, that it does not refer to anything outside of itself. But if music, in all its sensuous flux, does not mean anything in particular, might it still have a special kind of philosophical significance? In Deep Refrains, Michael Gallope draws together the writings of Arthur Schopenhauer, Friedrich Nietzsche, Ernst Bloch, Theodor Adorno, Vladimir Jankélévitch, Gilles Deleuze, and Félix Guattari in order to revisit the age-old question of music's ineffability from a modern perspective. For these nineteenth- and twentieth-century European philosophers, music's ineffability is a complex phenomenon that engenders an intellectually productive sense of perplexity. Through careful examination of their historical contexts and philosophical orientations, close attention to their use of language, and new interpretations of musical compositions that proved influential for their work, Deep Refrains forges the first panoptic view of their writings on music. Gallope concludes that music's ineffability is neither a conservative phenomenon nor a pious call to silence. Instead, these philosophers ask us to think through the ways in which music's stunning force might address, in an ethical fashion, intricate philosophical questions specific to the modern world.
Keywords: Bloch, Ernest, : 1880-1959 : Criticism and interpretation; Adorno, Theodor W., : 1903-1969 : Criticism and interpretation; Jankélévitch, Vladimir : Criticism and interpretation; Deleuze, Gilles, : 1925-1995 : Criticism and interpretation; Guattari, Félix, : 1930-1992 : Criticism and interpretation; Music : Philosophy and aesthetics; Adorno, Theodor; Aesthetics of Music; Bloch, Ernst; Comparative Literature; Deleuze, Gilles; Guattari, Félix; Hegel, Georg Wilhelm Friedrich; Jankélévitch, Vladimir; Schopenhauer, Arthur; The Ineffable